Implementation Combination Cryptographic Algorithm Triangle Chain Cipher and Vigenere Cipher In Securing Data in Database - Arif, Ahmad; Perdana, Adidtya; Budiman, Arief (Sinkron : jurnal dan penelitian teknik informatika, 2021)
Data security is most important today, because the rampant data theft resulting in a lot of misuse of data by irresponsible parties so that it makes us anxious as data owners, for data storage it is usually stored in the database. From these problems the idea emerged to create a cryptographic system where the system can secure data by encrypting and decrypting also make data fully save and then the data owned by the user. This study aims to secure the data in the database by encrypting the original data without destroying the original data when later after decrypted. To perform this security, a cryptographic methodology is used with both of  method that is Vigenere Cipher and Triangle Chain Cipher algorithms which are implemented in the application because both of methodology have same root that is classical cryptographic. This application will later be used as a medium for users to secure their data in the database so that later data theft will not to be easy. After doing fully research that produces applications that can implement combination of Vigenere Cipher and Triangle Chain Cipher algorithms,data in the encrypted database field is safe because encryption has been done to the data.